Developing an Alternative Modernity: The Case of Pondok Modern Gontor - Rachel Kamilia Faradiba Nibal (Islamica: Jurnal Studi Keislaman, 2022)
The debate about the image of pesantren, considered far from Modernity, has become a new intellective space that can be started through a postmodernism perspective. The thought later brings forth an alternative understanding of Modernity itself because the pesantren Gontor has proven that a number of its cadres can adapt optimally to Modernity and technology so that their capabilities are widely recognized globally. Therefore, this article explores how the Postmodernism approach concerning the study of international relations science which has strong relevance to postcolonial conditions, takes fundamental control over the ongoing modernization, especially in the field of technology in a traditional religious education institution like pesantren Gontor, so that it can be categorized in Alternative Modernity. Furthermore, the writing of this article uses a qualitative method with a literature study that allows further research to be needed. This article concludes that the pesantren Gontor has succeeded in offering a strong combination of Indonesian and Islamic characters as an Alternative Modernity to the Islamic education system in Indonesia.